2012
DOI: 10.1002/chem.201102807
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selected Doping of Upconversion Luminescent Er3+ into SrTiO3 for Visible‐Light‐Driven Photocatalytic H2 or O2 Evolution

Abstract: A series of upconversion luminescent erbium-doped SrTiO(3) (ABO(3)-type) photocatalysts with different initial molar ratios of Sr/Ti have been prepared by a facile polymerized complex method. Er(3+) ions, which were gradually transferred from the A to the B site with increasing Sr/Ti, enabled the absorption of visible light and the generation of high-energy excited states populated by upconversion processes. The local internal fields arising from the dipole moments of the distorted BO(6) octahedra promoted ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 109 publications
0
36
0
Order By: Relevance
“…Raman spectroscopy in solid samples is extremely sensitive to local deviations from the average periodicity, thereby making this a valuable probe of local structure 4g,k. 19 All of the SnSb‐ Tt samples showed one characteristic Raman band at around 470 cm −1 (Figure 7, framed area) with a shoulder at higher wavenumber.…”
Section: Resultsmentioning
confidence: 99%
“…Raman spectroscopy in solid samples is extremely sensitive to local deviations from the average periodicity, thereby making this a valuable probe of local structure 4g,k. 19 All of the SnSb‐ Tt samples showed one characteristic Raman band at around 470 cm −1 (Figure 7, framed area) with a shoulder at higher wavenumber.…”
Section: Resultsmentioning
confidence: 99%
“…Shi and coworkers [55] synthesized a series of UC luminescent Er-doped SrTiO 3 (ABO 3 -type) photocatalysts with different initial molar ratios of Sr/Ti by a facile polymerized complex method. Er 3+ ions were gradually transferred from the A to the B site with increasing ratio of Sr/Ti.…”
Section: Recent Progress In Upconversion-assisted Photocatalysismentioning
confidence: 99%
“…Using a metal oxide as a host material is a possible alternative, as metal oxides such as ZnO and TiO 2 are highly stable in the ambient atmosphere. ZnO-TiO 2 oxides are a multifunctional material that have been used in gas sensors [26] and photocatalysts [27,28]. And, we have reported that the PL intensity is increased by mixing TiO 2 and ZnO in comparison to only TiO 2 or only ZnO [29].…”
Section: Introductionmentioning
confidence: 99%